The performance effects of board heterogeneity: what works for EU banks?. Issue 10 (2nd July 2020) - Arnaboldi, F.; Casu, B.; Kalotychou, E.; Sarkisyan, A.
ABSTRACT: We examine the impact of board heterogeneity on the performance of EU-listed banks in the wake of the global financial crisis. In a comprehensive set-up, we consider standard board features (type, tenure, size, and age of board members) as well as board diversity features (gender diversity, employee representation, internationalisation, and age diversity). We propose a diversity index, which summarises the different dimensions of diversity, and control for unobserved heterogeneity and reverse causality. Our analysis uncovers a complex relationship between board heterogeneity and bank performance, which is influenced by market conditions and by national culture. Overall board diversity does not seem to affect bank performance, but it does decrease performance variability during the Eurozone crisis and in countries culturally more open to diversity. Different board and diversity features have a positive impact on bank performance (size, tenure, and employee representation); the relationship is non-linear, with the effect of diversity being more relevant when there is a significant proportion of minority representatives. While substantial board internationalisation has a negative impact on bank performance, the presence of foreign directors appears to be less detrimental during the Eurozone crisis and in countries that are more welcoming towards diversity.